Identificação e mapeamento de públicos em Relações Públicas e Personas: uma união metodológica possível? (Intercom - Brazilian Journal of Communication Sciences, 2024)
This paper aims to evaluate the possibility of joining the perspectives of building personas and identifying and mapping publics in public relations. The exploratory-descriptive bibliographic research covered national and international publications. The theoretical approach related to publics brings authors who study the object, write about the concept and activity. The focus on personas brings some of the most recognized authors in this subject. It considered the quality of the description of the methodological processes of the references found between 2002 and 2020, in data bases such as the CAPES journal portal and Google Scholar. The paper concludes that the persona methodology adds value to the activity of identifying and mapping publics, as it improves and brings more reliability to the process in terms of data collection, analysis and presentation techniques.